Bi-Newton’s method for computing spectral projectors - Demyanko, K.V.; Nechepurenko, Yu.M. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2014)
An efficient Newton-like method for computing the spectral projector associated with a separated group of eigenvalues near a specified shift of a large sparse matrix is proposed and justified. A number of numerical experiments with a discrete analogue of the non-Hermitian elliptic operator are discussed.